The Homopolyatomic Sulfur Cation [S20]2+ - Janis Derendorf; Lara Heiderich; Carsten Jenne; Marc C. Nierstenhöfer (Inorganics)
Homopolyatomic cations of the main group elements and of the element sulfur, in particular, are used as tutorial examples to teach structure and bonding in inorganic chemistry. So far, the cations [S4]2+, [S8]2+, [S19]2+, [S5]•+, and [S8]•+ are known experimentally. In this report, the generation and crystal structure determination of the salt Na2[S20]2[B12Cl12]3, containing the new homopolyatomic sulfur cation [S20]2+, is reported. The structure of the latter cation consists of two seven-membered homocycles, which are bridged by a six-membered sulfur chain. This structure is strongly related to that of [S19]2+. The heptasulfur rings show pronounced bond alternation. Comparison with the experimental structures of [S7X]+ (X = I, Br) and the application of quantum chemical calculations show unambiguously that the observed structural features are intrinsic properties of the cationic cyclo-heptasulfur moieties. The latter can occupy different conformations, which only slightly differ in energy. Charge delocalization and negative hyperconjugation contribute to the stability of the observed structures. The discovery of the [S20]2+ cation fits well into range of known homopolyatomic sulfur cations, which can be classified by their averaged oxidation state of sulfur.